An Analysis of Figurative Language in Poetry by Maya Angelou - Asmara Nengke Anggiamurni (PANYONARA: Journal of English Education, 2020)
Figurative language is used to beautify literary work especially the poems. It can make the poems more interesting and unique. But some readers cannot identify figurative language used in poetry. The poem’s readers, read, analyze, and interpret poetry without considering the use of figurative language. The objectives of the research were to explain the kinds of figurative language used in selected poems by Maya Angelou and to explain how the use of figurative language in Maya Angelou's poems. This is qualitative research with content analysis. This approach offered to analyze data by choosing some poems by Maya Angelou, reading the poems, identifying the figurative language used in the poems, then analyzing the figurative language used in the poems. In the stage of analyzing figurative language in the Maya Angelou’s poems, the researcher was grouping them based on the figurative language used in each poem. In analyzing data, the researcher analyzed every figurative language that is found in the poems and the last drawing conclusion based on the result of data analysis. This research revealed that there were figurative languages in every selected poem by Maya Angelou. Figurative languages used in the poems were varying. Each poem had characteristics so that the use of figurative language was also diverse. This research will give advantages for the readers especially to the lectures and the college students, and it is hoped that will be more research which analyzes figurative language not only in poetry but also in another literary work